2017
DOI: 10.1039/c6cp07537a
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte-controlled discharge product distribution of Na–O2batteries: a combined computational and experimental study

Abstract: Tuning the composition of discharge products is an important strategy to reduce charge potential, suppress side reactions, and improve the reversibility of metal-oxygen batteries. In the present study, first-principles calculations and experimental confirmation were performed to unravel the influence of O pressure, particle size, and electrolyte on the composition of charge products in Na-O batteries. The electrolytes with medium and high donor numbers (>12.5) are favorable for the formation of sole NaO, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 101 publications
0
14
0
Order By: Relevance
“…Many research groups have intended to design available cathodes and electrolytes for Na-O 2 battery. [4,[22][23][24] However, little attention was paid to the problematic Na anode.…”
Section: Introductionmentioning
confidence: 99%
“…Many research groups have intended to design available cathodes and electrolytes for Na-O 2 battery. [4,[22][23][24] However, little attention was paid to the problematic Na anode.…”
Section: Introductionmentioning
confidence: 99%
“…7 The sudden death of the cell chemistry is attributed to the formation of a passivation film between the cubic structures at the end of the discharge process, where the thickness is discharge rate dependent. 8 Although many factors based on NaO 2 growth and morphology have been reported including rate, 2,8,9 impurity concentration, 7,10 and solvent dependence, [11][12][13][14][15][16][17][18] a unified model of the fundamental control parameters of the discharge process remains unclear, with different conclusions operating under similar conditions being made. Although there has been an extensive review carried out by Bender et al 1 that ascertains the differences and similarities, Bi et al 19 analysed the cell setup concluding that glass cell setups afford different discharge products (mainly Na 2 O 2 Á2H 2 O) in comparison to stainless steel cell setups (NaO 2 only).…”
mentioning
confidence: 99%
“…The current increases at 4.0 V, highlighting further oxidation of the remaining reaction products. 12,16,24 The sequential description of the AFM images collected around the CV curve begins at the OCP (2.8 V) where the small striations of the freshly cleaved HOPG surface are observed that follow the step edges of the stacked graphene sheets, and the height profiles show that the step edges are 0.8 nm in height ( Fig. 1b and Fig.…”
mentioning
confidence: 99%
“…In fact, it has been demonstrated, by computational and experimental studies, that the nature of the electrolyte is able to control the distribution and morphology of the discharge products. Through thermodynamic calculations and the prediction of crystalline structures, it has been possible to establish the important role of the electrolyte [45]. More specifically, in the design of the correct electrolyte it is of vital importance to analyze the donor number (DN) associated with the electrolyte.…”
Section: Instability Of Electrolytementioning
confidence: 99%
“…Even so, most of the published studies analyze the stability of the species in the electrolyte as a function of the DN of the solvent. Wang et al determined that a high DN (> 12.5, which is the situation of the glymes commonly used as solvents) guides the formation of NaO 2 , while a DN below that limit can favor the NaO 2 -Na 2 O 2 mixture [45].…”
Section: Instability Of Electrolytementioning
confidence: 99%